A Markov chain model for daily rainfall occurrences at east Thanjavur district - THIYAGARAJAN, M.; DOSS , RAMA; RAJ, RAMA (MAUSAM, 1995)
The occurrences and non-occurrences of the rainfall can be described by a two-state Markov chain. A dry date is denoted by state 0 and wet date is denoted by state 1. We have taken the sample which follows a Poisson process with known parameter. Using this Poisson sample we have given a new approach to affect statistical inference for the law of the Markov chain and state estimation concerning un-observed past values or not yet observed future values. The paper aims at comparing the earlier fit of the data with the new approach.